2020
DOI: 10.24014/jti.v6i1.9468
|View full text |Cite
|
Sign up to set email alerts
|

Pengoptimalan Biaya Transportasi dengan Metoda North West Corner (NWC) dan Stepping Stone (SS) untuk Distribusi Produk Farmasi

Abstract: Model transportasi diadopsi untuk pengendalian operasi pabrik, penentuan daerah penjualan, pengalokasian lokasi distribusi dan pergudangan. PT. XYZ adalah salah satu perusahaan multinasional yang memiliki core business dibidang industry farmasi. Model optimasi merupakan salah satu model analisis sistem yang diidentikkan dengan operation research. penelitian ini menggunakan Northwest corner method (NWC)untuk memberikan prioritas pengalokasian dari pojok kiri atas matriks transportasi. Stepping Stone Method (SS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results showed that transportation costs using the Stepping Stone method were lower at IDR 13,341,654,000 than using the North West Corner at IDR 21,394,461,000. The results of research by Nteseo et al [20] showed the same results as [19], where Nteseo used two methods, namely the northwest corner and stepping stone, to determine the distribution cost of 3 kg LPG cylinders, with smaller stepping stone results compared to the northwest corner. Furthermore, their research results from Imbang [21] use the North West Corner method to obtain material distribution costs for the construction of the laboratory building of the Faculty of Engineering, Sam Ratulangi University [20], [21].…”
Section: Introduction Orona Virus (Covid-19mentioning
confidence: 74%
See 1 more Smart Citation
“…The results showed that transportation costs using the Stepping Stone method were lower at IDR 13,341,654,000 than using the North West Corner at IDR 21,394,461,000. The results of research by Nteseo et al [20] showed the same results as [19], where Nteseo used two methods, namely the northwest corner and stepping stone, to determine the distribution cost of 3 kg LPG cylinders, with smaller stepping stone results compared to the northwest corner. Furthermore, their research results from Imbang [21] use the North West Corner method to obtain material distribution costs for the construction of the laboratory building of the Faculty of Engineering, Sam Ratulangi University [20], [21].…”
Section: Introduction Orona Virus (Covid-19mentioning
confidence: 74%
“…Many researchers have used all three methods of solving the problem. Hasanah et al [19] used the northwest corner and stepping stone methods for pharmaceutical product distribution. The results showed that transportation costs using the Stepping Stone method were lower at IDR 13,341,654,000 than using the North West Corner at IDR 21,394,461,000.…”
Section: Introduction Orona Virus (Covid-19mentioning
confidence: 99%
“…Model transportasi merupakan cara menentukan rencana biaya terendah untuk mengirimkan barang dari satu sumber ke tujuan lainnya (Hasanah, T. U., 2020) sehingga transportasi dalam dunia industri merupakan salah satu bagian terpenting. Masalah transportasi membicarakan cara pendistribusian suatu barang dari sejumlah sumber (origin) ke sejumlah tujuan (destination).…”
Section: Pendahuluanunclassified
“…Menurut penelitian Nugraha dan Sari (2019) transportasi membicarakan cara pendistribusian suatu barang dari sejumlah sumber ke sejumlah tujuan. Masalah yang sering dihadapi terkait distribusi adalah membuat keputusan mengenai rute yang dapat mengoptimakan jarak tempuh atau biaya perjalanan, waktu tempuh, banyaknya kendaraan yang dioperasikan dan sumber daya lain yang tersedia (Fatimah, 2015). Saluran distribusi mempunyai tujuan untuk menyalurkan produk yang dihasilkan perusahaan dengan sasaran tempat tertentu diberbagai daerah geografis yang berbeda (Trisnani, 2017).…”
Section: Background 11 Introductionunclassified